Lucas Polynomial Approach for System of High-Order Linear Differential Equations and Residual Error Estimation - Cetin, Muhammed; Sezer, Mehmet; Guler, Coskun (HINDAWI LTD, 2015)
An approximation method based on Lucas polynomials is presented for the solution of the system of high-order linear differential equations with variable coefficients under the mixed conditions. This method transforms the system of ordinary differential equations (ODEs) to the linear algebraic equations system by expanding the approximate solutions in terms of the Lucas polynomials with unknown coefficients and by using the matrix operations and collocation points. In addition, the error analysis based on residual function is developed for present method. To demonstrate the efficiency and accuracy of the method, numerical examples are given with the help of computer programmes written in Maple and Matlab.
Keywords: COLLOCATION METHOD; NONLINEAR-SYSTEM; SOLVING SYSTEMS; APPROXIMATION; Engineering; Mathematics